Simultaneous Determination of Kirenol, Rosmarinic Acid and Caffeic Acid in Rat Plasma and Pharmacokinetic Study After Oral Administration of the Extract of Manxingshizhen Preparation by UPLC-MS/MS - Sun, Shuo; Zhang, Xue; Luo, Linda; Wang, Ping; Bai, Mengxuan; Yu, Jia; Guo, Xingjie (Current Pharmaceutical Analysis, 2019)
Introduction: A rapid, sensitive and convenient ultra-performance liquid chromatography with tandem mass spectrometric detection (UPLC-MS/MS) method has been validated and applied to the simultaneous determination of kirenol, rosmarinic acid and caffeic acid after oral administration of the extract of Manxingshizhen preparation in rat plasma. Materials and Methods: Puerarin was selected as the internal standard (IS). The plasma sample preparation was pretreated by liquid-liquid extraction of the mixture with ethyl acetate. All analytes were simultaneously detected in multiple reaction monitoring (MRM) mode via both the positive electrospray ionization (ESI+) and negative electrospray ionization (ESI-). In the experiment, all calibration curves revealed good linearity (r > 0.999). The LLOQ were between 0.80-2.00 ng/mL, respectively. Besides, the intra-day and inter-day precision ranged from 6.4 to 13.8%, respectively. Moreover, the accuracy was within - 11.4% and 12.8% for all the QC levels of all analytes. The extraction recoveries of the analytes and IS in plasma at three concentration levels ranged from 88.5 to 103.2%, moreover, the matrix effects of all the analytes and the IS were found to be satisfied with the acceptable range of 89.8%-101.7%. Meanwhile, the RSD values of stability met the requirement of not more than 15%. Furthermore, the pharmacokinetic parameters of three compounds were analyzed using concentrationtime profiles. Conclusion and Results: Plasma concentrations of the three compounds were determined up to 24 h after oral administration, and their pharmacokinetic parameters were in agreement with previous studies. The validated method was successfully applied in a pharmacokinetic study in rat plasma after oral administration of Manxingshizhen preparation.
Keywords: rat plasma